Power Optimisation of Centrifugal Pumps in a 4-Storey Building - Effendi, Riki; Rijal Siswanto, Ahmad; Qadri, Munzir; Hendra, Franka; Yunus Nasution, Ahmad (DINAMIS, 2025)
The optimization of water distribution systems in high-rise buildings is essential for enhancing energy efficiency and reducing operational costs. This study examines the effects of implementing a Variable Frequency Drive (VFD) on a centrifugal pump system within a four-storey high-rise building at PT SBA. A case study approach was employed to measure key operational parameters—namely, electrical power consumption, water flow rate, and pressure distribution—both before and after VFD installation. The experimental results demonstrate that the VFD application resulted in a 20% reduction in power consumption, decreasing from 3.5 kW to 2.8 kW, while the water flow rate improved by 12.5%, rising from 80 LPM to 90 LPM. In addition, the pressure range was significantly stabilized, narrowing from 1.2–2.5 bar to 1.0–2.0 bar across the building’s floors. An economic analysis based on the observed energy savings indicates an annual cost reduction of approximately Rp7,665,000, with a corresponding return on investment achieved in less than one year. The findings suggest that integrating VFD technology into centrifugal pump systems not only enhances operational efficiency and extends equipment lifespan by mitigating load fluctuations but also offers substantial economic benefits. This study provides a robust framework for the broader application of VFD-based optimization strategies in high-rise and industrial water distribution systems.